IMAGERY ANALYSIS IN WILLIAM SHAKESPEARE’S SONNETS - Jimmi Jimmi (Wanastra: Jurnal Bahasa dan Sastra, 2016)
The purpose of this paper is to analyze and to identify a literary work of an imagery which is found in Sonnet of William Shakerspeare by using qualitative method. Imagery is an image that symbolizes the object in poem and another literary work through the human’s sense, thought, and action by vigurative language. The writer also does some steps, such as collecting data, reading the sonnet more than once to get the meaning, analyzing the datas and making conclussion. The data are collected from the relevant references books, websites, and some articles. In the discussion, the writer analyzes the type of imagery that is found in the sonnets and discusses the meaning of each imagery found. The results of this analysis are about the imagery that is found in William Shakespeare’s sonnets which is divided by some type of imagery, they are: visual imagery, kinesthetic imagery, olfactory imagery, auditory imagery, organic imagery, and thermal imagery, also the meaning of each of them.